Insight into Essential and Complex Autism Spectrum Disorders: Clinical Characteristics, Chromosomal Microarray Analysis, and Risk Factors - Beyhan Tüysüz; Evrim Çifçi Sunamak; Gizem Durcan; Birol Öztürk; Dilek Uludağ Alkaya; Hazal Cansu Çulpan; Mehmet Barış Korkmaz; Burak Doğangün; Ertuğrul Kıykım (Genes, 2026)
Background/Objectives: Autism spectrum disorder (ASD) can present with either an essential or a complex phenotype. The aim of this study was to compare clinical characteristics and the diagnostic yield of copy number variations (CNVs) in essential and complex phenotypes, and to evaluate risk factors. Methods: A total of 163 Turkish children (126 boys, 37 girls) who met the DSM-5 diagnostic criteria for ASD were evaluated. Chromosomal microarray analysis was performed. Results: Among the patients, 21.5% had a complex phenotype and 78.5% had an essential phenotype. Overall, 13.7% of the patients had a developmental/intelligence quotient (DQ/IQ) below 50, most of whom had a complex phenotype. In contrast, 15.3% of the patients had a DQ/IQ of 70 or higher, all of whom had an essential phenotype. The frequency of verbal individuals was 30.5% and did not differ between the two phenotypes. Pathogenic CNVs were identified in 7.4%; 17.1% of the complex group and 4.7% of the essential group. CNVs of uncertain significance that were potentially causal because they included an ASD-associated gene were present in 12.3% of individuals. CNV positivity was significantly higher in individuals with an IQ below 50; interestingly, it was similar between the verbal and non-verbal groups. Besides ultra-rare CNVs, recurrent CNVs associated with ASD were identified. A novel pathogenic CNV was identified at 2q13.33, including NPHP1 and BUB1, both of which are expressed in the brain and are potentially associated with ASD. Advanced parental age and preterm birth were identified as possible risk factors. Conclusions: Deep phenotyping is important for the management of both essential and complex phenotypes and allows the identification of patients with a higher probability of having CNVs. Reporting novel or rare CNVs contributes to clarifying the pathogenesis of ASD.